Kepemimpinan Melayani Kepala Sekolah Kristen di SMA Negeri 1 Sipoholon - Vemberika Sianipar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine the servant leadership of the Christian principal at SMA Negeri 1 Sipoholon. The method used in this research is a descriptive quantitative method. The population consists of all 37 teachers at SMA Negeri 1 Sipoholon, all of whom were included as research respondents. Data were collected using a positive closed-ended questionnaire consisting of 30 items. Prior to conducting the study, the questionnaire items were tested on 30 teachers at SMA Negeri 1 Siborongborong, with the results showing that all items were valid and reliable.The results of the data analysis indicate that the percentage of servant leadership of the Christian principal at SMA Negeri 1 Sipoholon is 86.15%, which falls into the “good” category. Therefore, H0 is rejected and Ha, which states that there is a good level of servant leadership of the Christian principal at SMA Negeri 1 Sipoholon, is accepted.